2020
DOI: 10.3389/fped.2020.00030
|View full text |Cite
|
Sign up to set email alerts
|

Early Neonatal Pain—A Review of Clinical and Experimental Implications on Painful Conditions Later in Life

Abstract: Modern health care has brought our society innumerable benefits but has also introduced the experience of pain very early in life. For example, it is now routine care for newborns to receive various injections or have blood drawn within 24 h of life. For infants who are sick or premature, the pain experiences inherent in the required medical care are frequent and often severe, with neonates requiring intensive care admission encountering approximately fourteen painful procedures daily in the hospital. Given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
107
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 226 publications
1
107
0
7
Order By: Relevance
“…Growing evidence indicates that early-life stressors have implications for the vulnerability to develop painful conditions later in life (Waller et al, 2020). In line with these findings, it has been shown that premature babies exposed to many painful procedures present marked neurodevelopment changes in the nervous system (Williams & Lascelles, 2020). Since anxiety, depression, childhood trauma and adult stressful life events are associated with increased risk of developing chronic pain states (Abdallah & Geha, 2017;Bayram & Erol, 2014), it is plausible that this increased risk is based on 5mC alterations caused by external stressors (Niederberger et al, 2017).…”
Section: Dynamics Of Dna Methylation In Response To Environmental Smentioning
confidence: 82%
“…Growing evidence indicates that early-life stressors have implications for the vulnerability to develop painful conditions later in life (Waller et al, 2020). In line with these findings, it has been shown that premature babies exposed to many painful procedures present marked neurodevelopment changes in the nervous system (Williams & Lascelles, 2020). Since anxiety, depression, childhood trauma and adult stressful life events are associated with increased risk of developing chronic pain states (Abdallah & Geha, 2017;Bayram & Erol, 2014), it is plausible that this increased risk is based on 5mC alterations caused by external stressors (Niederberger et al, 2017).…”
Section: Dynamics Of Dna Methylation In Response To Environmental Smentioning
confidence: 82%
“…There are increasing concerns of what could be the consequences of early life pain and how is it going to affect the infants as they grow? A growing body of evidence reports long-term consequences of early life pain in humans show the association between early life pain and long-term neurosensory, cognitive, and psycho-behavioral disorders [ 70 , 71 ]. However, without methods to subjectively measure the degree of pain, and with current uncertainty of the effect of analgesics and sedatives exposure in the developing nervous system, assessment of pain and how to best alleviate it remains an important issue to be addressed in the critical care of preterm neonates.…”
Section: Pain Control and Sedationmentioning
confidence: 99%
“…Os recém-nascidos experienciam vários procedimentos dolorosos, ainda, nas 24 horas de vida, como parte da rotina de cuidados neonatal, como várias injeções e colheita de sangue (1) . A exposição constante do recém-nascido a esses procedimentos pode, em longo prazo, comprometer o desenvolvimento neurológico e comportamental, e as evidências mostram que o controle da dor acarreta benefícios nas respostas fisiológicas, comportamentais e hormonais desse recém-nascido.…”
Section: Introductionunclassified